Towards a picture of tourists' happiness - Filep, S.; Deery, Margaret (Croatian National Tourist Board, 2010)
Happiness is a concept with a long tradition in philosophy and is central to understanding the meaning of human life. Research on happiness has lately flourished in many social sciences. Yet in tourism studies this concept is underexplored. This lack of attention is surprising as tourism is increasingly seen in the literature as more than a break from everyday routines. It is today more and more seen as a health and well-being activity. The discussion in this article hence complements, but differs from, recent examinations of wellness and quality of life of tourists. In this article an exploratory picture of tourists' happiness is created. The picture of tourists' happiness is created by first discussing how tourists' happiness can be interpreted; and then by discussing how tourists' happiness can be evaluated in the main phases of the travel experience-anticipatory, on site, and reflective phases. It is concluded that tourists' happiness is a state in which the tourist experiences positive emotions (joy, interest, contentment, and love), is engaged in and derives meaning from holiday activities. This conceptualization is based on a theory from positive psychology-a field from psychology that empirically assesses happiness. Tourists' positive emotions, engagement, and meaning can be evaluated through analyses of tourist motivation and satisfaction in the three tourist experience phases. Examples of analysis methods are: narratives of perfect days and cognitive maps for assessments of positive emotions, special in-depth interviews to capture engagement at tourist sites, and specific qualitative measures of meaning derived from holidays. The interpretation and the assessment approaches form an exploratory picture of tourists' happiness. This picture is important as it sheds light on the personal value and quality of tourist experiences to individuals.